2019
DOI: 10.3233/jad-190216
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Authorships of Alzheimer’s Disease and Dementia Research Articles

Abstract: Background: Alzheimer's disease and dementia are an increasing burden affecting more than 50 million patients worldwide. Hence, research has increased significantly in recent decades. It is recognized that female authors are systematically underrepresented in research in general. Objective: In this article, we examine gender disparities in academic research on dementia and Alzheimer's disease in the last decade. Methods: 104,858 male and female authorships from 37,961 original research articles were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Gender parity and authorship diversity are declared goals in the publishing world in academic medicine (Clark and Horton 2019;Upthegrove et al 2021). Data on gender distribution in authorship in mostly high-impact Englishlanguage journals have been published for different medical specialties either focusing on their field (Shah et al 2021;Thelwall 2020) or on specific journals (Campbell et al 2019), disorders (Menzel et al 2019), study designs (Mehran et al 2021), or publication types (Mamtani et al 2020). The percentages of female authors in original research articles differ between medical specialties and range from about one-quarter to two-thirds with smaller rates of female first and senior authors in the fields of, e.g., cardiology (Asghar et al 2018) and anesthesia (Pagel et al 2019) in contrast to a larger female participation in, e.g., pediatrics (Fishman et al 2017) and dermatology (Bendels et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gender parity and authorship diversity are declared goals in the publishing world in academic medicine (Clark and Horton 2019;Upthegrove et al 2021). Data on gender distribution in authorship in mostly high-impact Englishlanguage journals have been published for different medical specialties either focusing on their field (Shah et al 2021;Thelwall 2020) or on specific journals (Campbell et al 2019), disorders (Menzel et al 2019), study designs (Mehran et al 2021), or publication types (Mamtani et al 2020). The percentages of female authors in original research articles differ between medical specialties and range from about one-quarter to two-thirds with smaller rates of female first and senior authors in the fields of, e.g., cardiology (Asghar et al 2018) and anesthesia (Pagel et al 2019) in contrast to a larger female participation in, e.g., pediatrics (Fishman et al 2017) and dermatology (Bendels et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with other studies, both within family medicine and other specialties. 6,7,[16][17][18][19][20][21][22][23][24][25]8,[26][27][28][29][33][34][35][36][37][9][10][11][12][13][14][15] This raises the question of why there are not comparable increases in the percentage of women in leadership. 40 There are signs of a narrowing gap between the genders within academic family medicine: this study shows better representation in senior authorship, which echoes the AAMC data on academic rank (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has to be mentioned, that multiple approaches on gender analysis have been published [22]. However, to the best of our knowledge, all approaches are limited due to invalid input data, as authors information are often invalid and names are not always predicting authors gender, especially in Asian countries [8,22,23]. Hence, for the best possible evidence, authors need to be identified manually, as it was done in the present analysis.…”
Section: Discussionmentioning
confidence: 99%